Pengembangan Instrumen Asesmen Kompetensi Perawat Klinis Berbasis The Six Dimensions Of Clinical Competency Dengan Media Website - Wati, Shofiyah (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2024)
Competency assessment instruments for nurses encompass all aspects necessary to provide safe, effective, and quality services. The purpose of that study was to develop a competency assessment instrument for clinical nurses based on the six dimensions of clinical competency using a website as the medium. The research design employed the Research and Development approach and was conducted in two stages. Stage 1, the following activities were carried out: 1) instrument evaluation through literature and field studies, data collected through interviews, observation sheets, and document reviews involving 4 nurse assessors with a sample size of 372 forms. 2) instrument development through Focus Group Discussions (FGD) with 10 managerial nurses and assessors, along with consultations with two nursing experts and one IT expert. 3) Validity testing using Content Validity Index (CVI) and reliability testing using KR20. Stage 2 involves the instrument development results that were recommended through FGD with 10 managerial nurses and assessors. Data analysis utilized descriptive analysis. Evaluation results indicated that the instrument had been last revised in 2017, with 30% incomplete fillings, 85% focusing on skill aspects, and still paper-based. The developed instrument, in the common component, added assessment filling instructions, and integrated the content of 12 core competencies into 6 clinical competency dimensions, utilizing a website as the medium. A CVI result of 1.00 indicates validity and a reliability result > 0.6 indicates reliability. The recommended instrument results could be applied. A new instrument was developed based on the theory of the six dimensions of clinical competency, integrating 12 core competencies. The developed medium is a website Keywords: Competency assessment, competency, clinical nurse, website